Students’ Perception of Teacher’s Code-Switching in Teaching English at Junior High School - Marsanda Preysli Siwu; Meily Ivane Esther Neman (CV. Edujavare Publishing, 2026)
This study aimed to investigate the level of students’ perceptions of teacher’s code-switching in teaching English at SMP UNKLAB. A descriptive quantitative design was employed, collecting data from 89 students through a questionnaire adapted from Aminah (2022). The findings revealed that the overall level of students’ perception was positive (M = 3.92). Specifically, the results for each indicator were interpreted as positive: receiving of stimulus (M = 3.92), understanding (M = 4.00), and evaluation (M = 3.86). These results indicate that students find teacher’s code-switching to be a helpful strategy that supports their comprehension and motivation in class. In conclusion, code-switching is perceived as a valuable instructional tool to bridge language barriers. Therefore, it is recommended that English teachers use code-switching strategically to clarify complex materials while maintaining sufficient English exposure for students.